Скоростные мониторы на базе лазеров на парах металлов - Тригуб М. В. Максим Викторович; Евтушенко Г. С. Геннадий Сергеевич; Губарев Ф. А. Фёдор Александрович; Суханов В. Б. Виктор Борисович; Торгаев С. Н. Станислав Николаевич (2010, 2010)
В фонде НТБ ТПУ отсутствует